2019
DOI: 10.5812/aapm.88327
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Pain Relief in Two Non-Pharmacological Treatments in Patients with Partial Rotator Cuff Tears: A Randomized Trial

Abstract: Background Pain induction is the primary characteristic of a rotator cuff tear while muscle weakness appears as a secondary feature, leading to further disability. Objectives The study aimed to determine the effectiveness of physiotherapeutic interventions through transcutaneous electrical nerve stimulation (TENS) or microcurrent electrical nerve stimulation (MENS) in conjunction with kinesiotherapy in patients with partial thickness rotator cuff tear. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…First, these findings underscore the importance of exercise-based conservative therapies in enhancing patient outcomes and restoring shoulder function. This hypothesis has been consolidated in recent years, as shown by the results of a recent meta-analysis, 38 which indicated that supervised physiotherapy leads to considerable improvements in pain reduction, range of motion, and shoulder function. Similarly, an RCT demonstrated the efficacy of kinesiotherapy in improving strength and functional outcomes in patients with PT-RCTs 43 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…First, these findings underscore the importance of exercise-based conservative therapies in enhancing patient outcomes and restoring shoulder function. This hypothesis has been consolidated in recent years, as shown by the results of a recent meta-analysis, 38 which indicated that supervised physiotherapy leads to considerable improvements in pain reduction, range of motion, and shoulder function. Similarly, an RCT demonstrated the efficacy of kinesiotherapy in improving strength and functional outcomes in patients with PT-RCTs 43 .…”
Section: Discussionmentioning
confidence: 94%
“…Regarding the Level of Evidence, 5 studies were level I RCTs 30,31,34,37,38 ; 5 level III PCC studies 7,8,32,33,42 ; and 1 level IV prospective case-series study 36 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further 70 articles were removed based on the screening of abstracts. After screening of full texts, 17 prospective randomised controlled trials were included within this review [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. A summary of the elimination process can be found in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Microcurrent therapy has an unrealised potential in healing dysfunctional tissue because of its ability to mimic weak, natural bioelectric ‘injury currents’, and subsequently enhance wound repairing (Poltawski and Watson 2009 ). In addition, within the clinical setting MCT has been widely applied in patients to reduce and relieve sinus pain (Goldsobel et al 2019 ; Maul et al 2019 ), chronic scar pain and itch from skin scars (Perry et al 2010 ; Ud-Din et al 2013 ), chronic back pain (Lerner and Kirsch 1981 ), and partial rotator cuff tears related pain (Vrouva et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%